An opportunity to form a Joint Venture between KPMG Europe LLP and Tata Consultancy Services - Pinto, Ajay Don (2012)
This report is part of the group management project and this is an individual write up reviewing a different aspect of the group project. The group project involved analysing six companies for the high tech services vertical. As the depth of the report is a function of time and resource constraints, the scope of the project was narrowed down to the largest revenue generating division in these companies. While this approach helped the group report to focus on the largest revenue generator, the group had to ignore other divisions which promised a much higher growth rate. The companies were analysed from a core competency view of the firm and areas were sought which could be outsourced. Newer divisions which were an extension of their core competencies and in the development stage had to be overlooked for time constraints. One of these companies the group analysed namely KPMG Europe LLP had extended their core competency and developing their business in management consulting. This report will analyse the management consulting division to identify how they and Tata Consultancy Services can benefit from each other.